Plasma Rivaroxaban Level in Patients With Early Stages of Chronic Kidney Disease—Relationships With Renal Function and Clinical Events - Sin, Chun-Fung; Wong, Ka-Ping; Wong, Hoi-Man; Siu, Chung-Wah; Yap, Desmond Y. H. (Frontiers in Pharmacology, 2022)
Introduction Drug accumulation of rivaroxaban is a concern in patients with chronic kidney disease (CKD). Data regarding the plasma rivaroxaban levels in early CKD patients and its relationship with clinical events is lacking. Methods Early CKD patients (Stage 1-3) with atrial fibrillation who received rivaroxaban (15 mg or 20 mg daily) were recruited. Plasma rivaroxaban levels were measured at 2 hours (peak) and 24 hours (trough) after drug administration, and correlated with eGFR and clinically significant events during the follow-up period (1 January 2018 to 31 October 2021). Results Ninety-two patients were included (CKD stage 1 n=10, stage 2 n=53, stage 3 n=29). Plasma trough levels in patients with stage 3 CKD were significantly higher than those with stage 2 and 1 CKD (66.0±34.9 ng/ml vs 35.7±24.7 ng/ml vs 34.7±26.2 ng/ml respectively, p=0.005), and showed inverse relationship with eGFR (r=0.391, p=0.001) in patients receiving 20 mg daily. The plasma trough rivaroxaban level correlated with PT and APTT (r=0.650 and 0.44 respectively, p<0.001 for both). Plasma trough rivaroxaban level in those with bleeding were higher than those who did not (59.9 ± 35.6 ng/ml vs 41.1±29.2 ng/ml, p=0.011), and multivariate analysis suggested that plasma trough rivaroxaban level was associated with the rate of bleeding complications (OR: 1.020, 95% CI 1.002-1.038, p=0.028). Conclusion Plasma trough rivaroxaban levels correlated with renal function in early CKD patients, and its measurement may help dosage optimization in patients with renal impairment. Moreover, our data suggests that there may be an association between plasma trough rivaroxaban level and the rate of bleeding complication.